2023
DOI: 10.1002/aic.18241
|View full text |Cite
|
Sign up to set email alerts
|

Janus particle amphiphilicity and capillary interactions at a fluid interface

Elton L. Correia,
Sepideh Razavi

Abstract: Studying the behavior of anisotropic particles at fluid interfaces is a rapidly expanding field, as understanding how the introduced anisotropy affects the resulting properties is essential in the engineering of interfacial systems. Surface anisotropic particles, also known as Janus particles (JPs), offer new possibilities for novel applications due to their amphiphilicity and stronger binding to fluid interfaces compared to homogeneous particles. Introducing surface anisotropy creates complexity as the orient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 101 publications
0
2
0
Order By: Relevance
“…In addition to their impact on surface wettability, NPs can influence the rheological properties of fluid–fluid interfaces depending on their size, shape, surface roughness, and anisotropy, which can be employed in tuning the stability of emulsions and foams. , Among different types of NPs, Janus particles (JPs) stand out, as they combine surface anisotropy and amphiphilicity into a single particle. Because one face of the JPs is hydrophilic and the other is hydrophobic, they exhibit special properties at fluid interfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to their impact on surface wettability, NPs can influence the rheological properties of fluid–fluid interfaces depending on their size, shape, surface roughness, and anisotropy, which can be employed in tuning the stability of emulsions and foams. , Among different types of NPs, Janus particles (JPs) stand out, as they combine surface anisotropy and amphiphilicity into a single particle. Because one face of the JPs is hydrophilic and the other is hydrophobic, they exhibit special properties at fluid interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Since the surface anisotropy of JPs can be controlled, the resulting interfacial properties of the particle network can be tuned. Razavi et al showed that the amphiphilicity of JPs controlled their collapse behavior at the air–water interface under applied compressive stress, a behavior which was attributed to the orientation of particles and interparticle capillary interactions as the JP amphiphilicity was modified . In addition to experimental investigations, simulations may offer an opportunity to carry out numerical experiments, allowing systematic changes in NP properties and leading to significant contributions to the study of NP characteristics.…”
Section: Introductionmentioning
confidence: 99%